Lignan-containing maple products inhibit Listeria monocytogenes biofilms on fresh produce - Elbakush, Ahmed M.; Fulano, Alex M.; Gomelsky, Mark (Frontiers in Microbiology, 2023)
Major listeriosis outbreaks have been associated with fresh produce contaminated with Listeria monocytogenes. Strains that synthesize the Pss exopolysaccharide (EPS) have an estimated 102 to 104-fold advantage over nonsynthesizing strains in causing listeriosis. They more readily attach to the surfaces of fruit and vegetables forming EPS-biofilms that better withstand stresses associated with produce storage and consumption. Here, we show that the threat to fresh produce safety posed by the listerial EPS-biofilms may be countered by broadly available maple products. We serendipitously discovered that aqueous extracts of wood from several Acer (maple) and Carya (pecan, hickory) species inhibit the formation of listerial EPS-biofilms without affecting bacterial viability. One active ingredient in maple wood was identified as nortrachelogenin-8’-O-β-D-glucopyranoside (NTG). At 120 μM, this lignan decreased colonization of the EPS-synthesizing L. monocytogenes on cantaloupe pieces by approximately 150-fold, and on cut celery and lettuce by 10 to 11-fold. Another lignan, lariciresinol, which is abundant in a common food sweetener, maple syrup, had antibiofilm activity comparable to that of NTG. Diluted in the range of 1:200 to 1:800 maple syrup from two random manufacturers prevented formation of listeiral EPS-biofilms. Importantly, not only did maple products drastically decrease colonization of fresh produce by the EPS-synthesizing strains, they also decreased, by 6 to 30-fold, colonization by the L. monocytogenes strains that do not synthesize measurable EPS, including strains from the infamous 2011 cantaloupe listeriosis outbreak. Inhibition of surface colonization by various listerial strains, broad availability of maple sap and syrup as well as maple lumber processing waste position maple products as potential antibiofilm agents for protecting fresh produce from L. monocytogenes.